Entrance of the garbhagriha of the Mandaleshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
The entrance of the garbhagriha (sanctum sanctorum) of the Mandaleshwar Mahadev Temple is marked by an ornate dvarashakha (door jamb). Seen here is the view of the garbhagriha entrance from the mandapa of the temple. The dvarashakha is of the trishakha (with three vertical bands) variety, profusely carved with sculptures and geometric designs. The lalatabimba (lintel) has a sculpture of Ganesha. The three shakhas (vertical bands) of the dvarashakha are a patri (foliage) shakha, a shakha of maladharas (garland bearers) and one shakha with deities and ghatpallava (pot with foliage) motif.